Anew yellow-flesh nectarine cultivar Zhongnong Zhenzhu 4 - WANG Yingying; LIU Lichang; LIU Zhiwu; YANG Xingwang; WANG Xiaodi (Guoshu xuebao)
Zhongnong Zhenzhu 4 is a mid-season yellow-fleshed nectarine cultivar that was developed through artificial hybridization between Zhongnong Zhenzhu and Zhongyou 16 in 2013 at the experimental field of Juxian Institute of Peach. A total of 105 hybrid seeds were produced from this cross. Initial selection took place in 2016, focusing on its excellent eating quality, appealing appearance, and high yield potential. Following comprehensive regional adaptability trials conducted in Rizhao and Linyi from 2018 to 2022, the cultivar was officially selected in 2022. It was registered and certified as a new plant variety from the Ministry of Agriculture and Rural Affairs in the same year, designated as Zhongnong Zhenzhu 4 with the variety code GPD peach (2022) 210037. The tree demonstrates moderate growth vigor and an open canopy, and is highly productive and consistently yielding, producing fruit that are flavorful, yellow-fleshed. Young branches exhibit a reddish-brown hue on the sunlit side and green on the shaded side, with an average internode length of 1.7 cm and double-flowered buds. The leaves are elliptical lanceolate, 11.5 cm in length and 3.9 cm in width, featuring circular serrations along the edges. The flowers are pink, self-pollinating, with glabrous ovary walls and equal-height stamens and pistils. The fruit is ovate, characterized by a yellow skin and a deep-red surface, with over 90% of the fruit's exterior covered in deep red. The suture line is moderately pronounced, and the two halves are relatively symmetrical. The flesh is yellow with red pigmentation surrounding the stone, with an average fruit weight of 76 g and a maximum weight of 96 g. At harvest, the flesh firmness of the mature fruit reaches 9.3 kg·cm-2. The soluble solid content (SSC) ranges from 14.0% to 16.0%, while the total acid content varies between 0.25% and 0.30%. The stone is easily separated, and the flesh is sweet. In Rizhao, bud break occurs in late March and lasts for 3-5 days. Fruit matures in mid-August, approximately 130 days post-bloom, and a harvesting period extends over 5 days. The fruit has a good storage performance, with a shelf life up to 5 days. The defoliation period occurs in late November, resulting in a total growth period of around 260 days. In comparison to its parent variety, Zhongnong Zhenzhu, the new cultivar Zhongnong Zhenzhu 4 matures approximately 10 days later and produces larger fruit. It begins fruiting in the second year following spring planting and achieves higher production levels by the fourth year. The cultivar exhibits stable yields and is well-suited for cultivation in Shandong Province and neighboring peach-growing regions. A Y-shaped training system is recommended for implementation in flat areas, with a spacing of (1.5-2.0) m × (4-5) m. All types of fruit-bearing branches can yield fruit, with medium and long fruit branches being predominant. Natural fruit set rates reach 70.3% without the presence of pollinizer trees, with yields potentially reaching up to 2500 kg per 666.7 m2. However, fruit thinning is crucial to maintain commercial quality and tree vigor, with a recommended spacing of 10 cm between fruits on the same side. To ensure optimal eating and commercial quality, yields should be controlled to below 1500 kg per 666.7 m2.